Effect of Oregano on Silicone Soft Denture Liner - Ariyani; Ricca Chairunnisa; Sherley Margan; Sherina Annastasya; Natalia Hotmauli Sianturi (TALENTA, 2024)
Silicone soft denture liner (SDL) is designed to absorb, reduce, and distribute pressure on denture-bearing tissues. The properties include a poor bonding strength to heat-polymerized acrylic resin base and surface roughness which promotes Candida albicans adhesion. SDL absorbs disinfectant solution during the immersion of denture in a disinfectant solution, leading to stiffness. Therefore, this study aimed to evaluate the effectiveness of oregano essential oil as an antimicrobial and the impact on the physical and mechanical properties of SDL. Antimicrobial test was conducted on 27 samples (3 groups) using disc diffusion methid and measured with a digital caliper, while surface roughness, elastic modulus, and bond strength test was performed on 20 samples (4 groups).. Surface roughness was evaluated with a profilometer. Furthermore, elastic modulus and bond strength were assessed using the universal testing machine (UTM). The results of one-way ANOVA test showed significant differences (p<0.05) in all groups of antimicrobial, surface roughness, elastic modulus, and bond strength tests showed significant differences (p<0.05). In conclusion, the addition of oregano essential oil to SDL, enhanced the antimicrobial properties, without compromising its physical and mechanical properties. Oregano extract is expected to be developed as a commercial product.